2015
DOI: 10.1007/s10522-015-9564-1
|View full text |Cite
|
Sign up to set email alerts
|

Skin pentosidine and telomere length do not covary with age in a long-lived seabird

Abstract: The questions about why and how senescence occurs in the wild are among the most pertinent ones in evolutionary ecology. Telomere length is a commonly used marker for aging, while other biomarkers of aging have received considerably less attention. Here we studied how another potent indicator of aging-skin pentosidine concentration-relates to age and blood telomere length in a long-lived seabird with well-documented reproductive senescence. We found no associations between telomere length, skin pentosidine and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 29 publications
2
18
0
Order By: Relevance
“…Concave relationship between white wing patch size and age indicates that it is a condition-dependent trait. Consistent with this, previous studies in the same colony have shown that middle-aged birds start their annual breeding attempts earlier (Rattiste et al 2015), lay heavier eggs and their breeding success exceeds that of young and old individuals (Rattiste 2004). Also consistent with an idea of condition dependency is the finding that females with larger white wing patches experienced lower extent of abrasion of wing tips.…”
Section: Statistical Analysessupporting
confidence: 84%
“…Concave relationship between white wing patch size and age indicates that it is a condition-dependent trait. Consistent with this, previous studies in the same colony have shown that middle-aged birds start their annual breeding attempts earlier (Rattiste et al 2015), lay heavier eggs and their breeding success exceeds that of young and old individuals (Rattiste 2004). Also consistent with an idea of condition dependency is the finding that females with larger white wing patches experienced lower extent of abrasion of wing tips.…”
Section: Statistical Analysessupporting
confidence: 84%
“…Absence of age-related decline in uropygial gland size in old birds compares favourably with results of previous studies (Rattiste et al 2015;Urvik et al 2016;Sepp et al 2017) indices of physiological condition is consistent with the concept that aging is multidimensional and can be asynchronous in wild animals (Hayward et al 2015). For instance, it has been shown, that in wild ungulates reproductive senescence may start later and progress more rapidly, than age-related declines in survival probability (Nussey et al 2013) and in some mammal species even post-reproductive survival has been documented (Croft et al 2015).…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies in this species have indicated that reproductive senescence is common in this colony, with old birds starting breeding later and having lower breeding success (Brommer and Rattiste 2008), lower investment into egg quality (Urvik et al 2018) and having smaller ornamental white wing patches (Sepp et al 2017) than middle-aged birds. At the same time, traits related to physiological condition (telomere length and skin pentosidine concentration; Rattiste et al 2015), and indices of oxidative and nutritional state (Urvik et al 2016), do not show consistent age-related patterns. These findings are compliant with the prediction of the life-history theory that in long-lived species whose lifetime reproductive success depends heavily on lifespan, self-maintenance is prioritized over reproduction (Nussey et al 2013).…”
Section: Introductionmentioning
confidence: 92%
“…Pentosidine has been shown to accumulate in a linear fashion in terrestrial birds and some seabirds including California gulls ( Larus californicus ) (Chaney, Blemings, Bonner, & Klandorf, ) and Double‐crested cormorants ( Phalocrocorax auritus ) (Fallon et al, ). This technique has yielded age estimates with a precision of 2–4 years in wild birds (Chaney et al, ; Fallon et al, ; Rattiste et al, ). However, in a study of another long‐lived seabird, the Bridled tern ( Onychoprion anaethetus ), no correlation between pentosidine levels and age was found (Labbé, ).…”
Section: Discussionmentioning
confidence: 99%